The analysis of social application of irony varieties in Atar-e- Nishaburi’sMosibatname - Hassan Soltani kohbanani; kamyar saydi (مطالعات زبانی و بلاغی)
Irony is one of the important and highly used term in the three fields of literal critics, philosophy and eloquence. There are many equivalent terms such as sarcasm, satire, quip, ridicule, etc. for it. But not of these equivalents are a comprehensive definition for it. The contrast between existence and representation is the simplest definition. However, more than this contrast, irony has other components that play crucial role in its creation. Mosibatname is one of the theosophical curtsy books in which he has used this artistic technique to present theosophical and social issues in varieties of patterns based on the readers’ understanding. Atar in a superior position than others, has deeply comprehended his contemporary issues. The authors, by carrying out this analysis, have understood that Atar has used different types of irony like situational, lingual, dramatic, and Socratic   in the structures of his stories. It can be said that the important reasons for using irony were flow of the story, expressing social and ethical concepts, political oppression, and Atar’s conservatism.